2009
DOI: 10.1007/s00464-009-0605-1
|View full text |Cite
|
Sign up to set email alerts
|

Routine management of stricture after gastric bypass and predictors of subsequent weight loss

Abstract: Initial dilation with a larger balloon is safe and may prevent stricture recurrence. Further study of modifiable risk factors for reduced weight loss after surgery, such as alcohol use, may improve patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Of the 18 studies describing the method of anastomosis, 12 (70.5%) used a circular stapler and, five of them, also used either manual suturing 20,24 or a linear stapler 17,28,29 . Four studies used a linear stapler only 4,18,22,26 and one study used manual suturing only 11 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 18 studies describing the method of anastomosis, 12 (70.5%) used a circular stapler and, five of them, also used either manual suturing 20,24 or a linear stapler 17,28,29 . Four studies used a linear stapler only 4,18,22,26 and one study used manual suturing only 11 .…”
Section: Resultsmentioning
confidence: 99%
“…Ryskina et al 24 reported that dilator type, and initial and maximum balloon size, were determined by the gastroenterologist at the time of the procedure. The literature did not establish a recommended time for dilation procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current era of divided RYGB, the majority of GGF are caused by poor surgical technique with failure to completely divide the stomach during pouch creation with maintenance of continuity between the pouch and remnant. In order to reduce the incidence of GGF some authors recommend a meticulous oversewing of staple lines, careful anastomotic technique with good bites of healthy tissue, avoidance of alimentary limb obstruction, and intraoperative confirmation of anastomosis integrity using methylene blue 34 .…”
Section: Methodsmentioning
confidence: 99%
“…Sequential balloon dilatation of a stricture is effective in restoring an adequate gastric outlet size, often over the course of multiple treatments . Expert gastrointestinal consultation is vital, and possibly surgical consultation.…”
Section: Casesmentioning
confidence: 99%